An Analysis of Marx’s Legacy in the Field of Communication Studies - Bahar Kayıhan (tripleC: Communication, Capitalism & Critique, 2018)
New communication technologies strengthen existing power relations, helping to maintain class inequalities and alienating people. In the new communication age, human subjectivity itself has become a commodity. This paper analyses the role of Marxist studies in the academic field of communication studies. It focuses on the relevance of Marx's views for understanding communication in the digital era, Marxist communication studies after the expansion of digital media, and new dimensions of communication that have been incorporated into Marxist literature. Topics that matter in this context include the intersection of play and work, media economics in the age of digital communication, digital labour, the online games industry, targeted advertising, newly emerging social inequalities, and surveillance and privacy issues. Also an outlook for potential future Marxist studies of communication is given.